2015
DOI: 10.1051/0004-6361/201425572
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic fields in the nearby spiral galaxy IC 342: A multi-frequency radio polarization study

Abstract: Context. Magnetic fields play an important role in the formation and stabilization of spiral structures in galaxies, but the interaction between interstellar gas and magnetic fields has not yet been understood. In particular, the phenomenon of "magnetic arms" located between material arms is a mystery. Aims. The strength and structure of interstellar magnetic fields and their relation to spiral arms in gas and dust are investigated in the nearby and almost face-on spiral galaxy IC 342. Methods. The total and p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
78
3
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(100 citation statements)
references
References 127 publications
(242 reference statements)
18
78
3
1
Order By: Relevance
“…As the vertical scale height of the halo magnetic fields of ∼6−7 kpc (e.g. Beck 2015) is similar to the assumed size of the hot gas halo (10 kpc), we do not expect a significant change of the magnetic energy density in the halo, especially when an uncertainty of its Notes. (a) η is the volume filling factor.…”
Section: Heating Of the Gas By Magnetic Reconnection?mentioning
confidence: 61%
See 1 more Smart Citation
“…As the vertical scale height of the halo magnetic fields of ∼6−7 kpc (e.g. Beck 2015) is similar to the assumed size of the hot gas halo (10 kpc), we do not expect a significant change of the magnetic energy density in the halo, especially when an uncertainty of its Notes. (a) η is the volume filling factor.…”
Section: Heating Of the Gas By Magnetic Reconnection?mentioning
confidence: 61%
“…Rudimentary magnetic arms were also found in other spiral galaxies (Beck 2015), but NGC 6946 still is the most prominent example.…”
Section: Introductionmentioning
confidence: 84%
“…We assume here equipartition between the magnetic energy density and cosmic rays, with the magnetic energy density given as a fraction ǫ B of the turbulent energy density. Indeed, observations have shown that the energy density of turbulence and the magnetic field are essentially comparable, implying ǫ B ∼ 1 (Beck 2007(Beck , 2015. The latter indicates that turbulence may play a central role in amplifying the magnetic field.…”
Section: Basic Assumptionsmentioning
confidence: 97%
“…The latter requires rather high Mach numbers, which may not be available in the interstellar medium (Guo et al 2014a), or the Firehose instability, if the acceleration only concerns the electrons (Guo et al 2014b). In that case, a high plasma beta would be required, while current estimates indicate that it may be rather small (Beck 2015).…”
Section: Introductionmentioning
confidence: 98%
“…Polarisation observations of synchrotron emission from nearby galaxies suggest that large-scale magnetic fields in galactic disks are predominantly spiral with roughly the same pitch angle both within spiral arms and in interarm regions (e.g. Beck 2015).…”
Section: Introductionmentioning
confidence: 99%